Psychotic symptoms and its associated factors relating to psychoactive substance use among the youth population in Northwest Ethiopia - Kassew, Tilahun; Tilahun, Sewbesew Yitayih; Alemayehu, Biruk Fanta; Getnet, Berhanie; Demilew, Demeke; Tarekegn, Gebrekidan Ewnetu; Alemu, Kassahun; Yesuf, Yassin Mohammed; Oumer, Mohammed; Mehari, Eden Abetu; Melkam, Mamaru; Nenko, Goshu (Frontiers in Psychiatry, 2023)
seventy-two youths who uses psychoactive substances were included in the study. The prevalence of psychotic symptoms was 24.2 % with 95% CI (20.1, 28.8). Being married [AOR=1.87 95%CI: 1.06, 3.48], recent loss of loved ones [AOR=1.97 95%CI: 1.10, 3.18], low perceived social support [AOR = 1.61 95%CI: 1.11, 3.02], and severe psychological distress [AOR = 3.23 95%CI; 1.64, 6.54] were the factors associated with psychotic symptoms among youths with psychoactive substances use at p<0.05. Conclusion: Psychotic symptoms related to psychoactive substances among the youth in Northwest Ethiopia were high. Thus, it is better to give special attention to the youth population with low social support and existing psychological distress concurrent with psychoactive substance uses.